2006
DOI: 10.1103/physrevlett.97.227201
|View full text |Cite
|
Sign up to set email alerts
|

Electric-Field Control of Exchange Bias in Multiferroic Epitaxial Heterostructures

Abstract: The magnetic exchange between epitaxial thin films of the multiferroic (antiferromagnetic and ferroelectric) hexagonal YMnO 3 oxide and a soft ferromagnetic (FM) layer is used to couple the magnetic response of the FM layer to the magnetic state of the antiferromagnetic one. We will show that biasing the ferroelectric YMnO 3 layer by an electric field allows control of the magnetic exchange bias and subsequently the magnetotransport properties of the FM layer. This finding may contribute to paving the way towa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
203
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 312 publications
(212 citation statements)
references
References 19 publications
6
203
1
Order By: Relevance
“…With the increase of the electric field, the magnetic anisotropy became stronger. Similar effect can be observed in Py/YMO herterostructure as well [31]. In 2013, Buzzi et al [32] observed a 90° rotation of magnetization due to the switching of out-of-plane ferroelectric polarization in artificial multiferroic nanostructures (arrays of Ni on PMN-PT substrates).…”
Section: Science China Materialssupporting
confidence: 52%
“…With the increase of the electric field, the magnetic anisotropy became stronger. Similar effect can be observed in Py/YMO herterostructure as well [31]. In 2013, Buzzi et al [32] observed a 90° rotation of magnetization due to the switching of out-of-plane ferroelectric polarization in artificial multiferroic nanostructures (arrays of Ni on PMN-PT substrates).…”
Section: Science China Materialssupporting
confidence: 52%
“…1a 17 . We image the magnetic structure of the CoFe layer at zero magnetic field using scanning electron microscopy with polarization analysis (SEMPA) 38 . By measuring the spin polarization of secondary electrons, SEMPA directly measures the local vector magnetization in the CoFe layer 39 .…”
Section: Resultsmentioning
confidence: 99%
“…The most promising single-phase MF materials to use as an AFM pinning layer are YMnO 3 and BiFeO 3 . ME control of the exchange bias has been demonstrated at YMnO 3 /NiFe interfaces [140]. However, this effect is irreversible and exists only at low temperatures.…”
Section: (C) Exchange Biasmentioning
confidence: 99%